A logic of efficient and optimal designs. (5th November 2019) - Primiero, Giuseppe
Abstract: Logics of design have been formulated until recently to offer systematic treatments of the way systems express the relation between resources, processes and their outputs. We present a logic of systems design which explicitly formalizes this relation as a decidable checking problem on resource access and define computable efficiency and optimality properties.